Driver Distraction: Breakdowns of a Multi-Level Control Process - John Lee (Journal of Road Safety)
Beginning with the introduction of the car radio, there have been concerns regarding how in-vehicle technology might undermine driving safety. Those concerns are particularly apparent today as many worry about the safety consequences of introducing vastly more complex technologies into the car, most prominently cell phones. Developments in the areas of wireless communication, computing, and GPS technology make an increasing variety of navigation, email, and internet systems available to the driver (Lee & Kantowitz, 2005). This availability, coupled with increased commute times, productivity pressures, and the diffusion of work beyond the office makes it likely that drivers will use these devices while driving. For example, 90% of all cell phone owners in the US report that they use the phone while driving (Goodman, Tijerina, Bents, & Wierwille, 1999) and 60% of total cell phone usage occurs while driving. The increasingly common use of existing technology and the rapidly emerging new technology make it imperative to understand how in-vehicle technology affects driving safety. Properly designed, the new technologies may enhance driving enjoyment and safety; poorly designed, they can be deadly.